State-driven Hate Speech: from Nazi Germany to Date - Marsili, M. (Freedom of Expression, Hate Speech, and Religious Freedom: A Human Rights Perspective, 2022)
Legal definitions of hate speech vary from country to country and is matter of both civil law and criminal law (hate crime). It is generally intended as a public speech that expresses hate or encourages violence towards a person or group based on something such as race, skin, colour, national origin, ethnicity, sex, gender identity, disability, religion, or sexual orientation. Nazi Germany is an instructive example of how far the hateful and extremist speech can go. The hate speech towards Jews – which comes from far away, at least from the Middle Ages – has never subsided, and is fueled by the confrontation with the Palestinians and the Arabs. On the other hand, over the last decade jihadist terrorism has triggered a wave of islamophobia in Europe, the biggest one after clash between Christians and Muslims in Middle Ages. Alongside situations that have grabbed the headlines and the attention of the world public opinion, there are "regional" issues of no less importance. The hate speech supports the ethnic cleansing – genocide for some – of the Muslim minorities in Myanmar (Rohingya), in Xinjiang, China (Uyghurs, a Turkic-speaking ethnic group, and other ethnic and religious minorities), and of Darfuri during the conflict in Western Sudan (2003-ongoing). In neighbouring India, the Hindu nationalists spread hate speech and incite violence against the Muslim community and other minorities. There are historical precedents, of which the Holocaust is the best known, showing that hate speech can be a precursor to atrocity crimes on a wider scale, including genocide, from Rwanda (1994, against the Tutsi) to Bosnia (1995, more than 7,000 Bosnian Muslim killed by Bosnian Serb forces in Srebrenica, Bosnia-Herzegovina) to Cambodia (1975-1979, in which approximately 1.7 million people, 21% of the country's population, were killed by the Communist group known as the Khmer Rouge). The present Russian question generates two-way hatred with Ukraine and the West, fueled by deep faking propaganda and cognitive warfare. This paper aims to shed light on the state-driven hate speech which is going on in some countries.